(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This interview with Diana Taylor, which took place at the Hemispheric Institute of Performance and Politics in August 2012, touches upon several issues. First Diana Taylor focuses on the innovative nature of Performance Studies, having as its object of study an object of analysis that is never given “a priori”, but that, instead, has to be created and circumscribed from time to time. In this sense she emphasizes the methodological effectiveness of Performance Studies in stepping forward as an analytical lens aiming at investigating various forms of behavior and “embodied” cultural practices, understood as forms of transmission of meaning. Secondly, turning the attention to the work done with her Hemispheric Institute of Performance and Politics, Diana Taylor highlights the political value inherent in the performative expressions and examines both the important connection between theory and practice in the field of Performance Studies, and the transdisciplinary or postdisciplinary dimension that characterizes it. Finally, reflecting on the ontology of performance, she affirms that, resulting from a mix of codes and conventions, performance never “happens” for the first time, and that any attempt to “save” or “preserve” it is intended to fail.